Practical Use of ICT course in Libraries: Perspectives of MLISc graduates in Nepal - Nyoupane, Bhabana; Nyaichyai, Lila (Contemporary Research: An Interdisciplinary Academic Journal, 2023)
Although the Central Department of Library and Information Science (CDLIS) was founded in TU 27 years ago, the Masters in Library and Information Science (MLISc) program is less popular among recent graduates. The MLISc program's reputation and significance are dependent on how successfully it has adapted to emerging information and communication technology (ICT). It is an early attempt to assess the MLISc ICT course material, primarily focusing on how applicable it is to real-world professional situations.Working librarians from Nepal participated in a focus group discussion to assess how well the MLISc ICT course applied to their line of work. Participants have suggested that the basic and advanced ICT course topics in the MLISc curriculum should be distinguished clearly. Library automation, digital library software, and other advanced ICT courses are available. However, the library profession places a high value on graduates with a complete understanding of information system architecture, library automation, and digitization services.